مرويات التابعي ميمون الكوردي في كتب السنة- جمع ودراسة - محمود, م. د. صباح رسول (Sulaimani Journal for Humanities, 2023)
Since the dawn of Islam, the Kurds and their scholars have contributed greatly to the construction of the Islamic civilization in all its aspects, especially the scientific and cognitive aspects. And since the honorable Sunnah of the Prophet is the second source after the Holy Qur’an, it had its own impact on them, so they cared about serving the honorable Prophet’s Sunnah with narration and knowledgeable, and they exerted the precious and in order to preserve it, understand it, and pass it on to the next generations. so Kurdish scholars have made great contributions in this field. Among these greats: the (Tabeiy) great Maymoon Al-Kurdi, the son of the (Sahaby) great Jaban Al-Kurdi. The owners of the books of the Sunnah Recorded down eight narrations (Hadeth) of this (Tabeie) venerable Kurdish, some of which are correct and others are weak, according to the rules of the noble Hadith science.
Keywords: Maymoon AlKurdi; Narratives; Tabeiy; Sunnah Books